Upaya Peningkatan Karakter Islami Anak Melalui Festival Anak Sholeh-Sholehah Di Desa Bungkuk Parang Magetan - Andhita Risko Faristiana; Ganes Biger Berlian Mahliga; Tiyas Indarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The rapid flow of globalization can have a negative impact on the morale of children as the next generation, and this must be addressed immediately by improving character in children. Islamic children's competition or sholeh-sholehah children's festival is one of the efforts to improve character in children, especially in Islamic character. This study aims to determine the implementation of sholeh-sholehah children's festival activities or Islamic children's competitions in improving Islamic character in children in Bungkuk Village, Parang, Magetan. The method used in this service research is the Asset Based Community Development (ABCD) method which prioritizes the utilization of assets or potentials owned. The results of this service research prove that the implementation of the sholeh-sholehah children's festival or Islamic children's competition in Bungkuk Village, Parang, Magetan can be one of the efforts to improve Islamic character in children. This can be seen from children who are more confident when doing the adhan, and more enthusiastic about memorizing short letters and daily prayers.